Is there a therapeutic window for pentoxifylline after the onset of acute pancreatitis? - Coelho,Ana Maria Mendonça (2012)
PURPOSE: To investigate the effects of pentoxifylline (PTX) in experimental acute pancreatitis (AP) starting drug administration after the induction of the disease. METHODS: One hundred male Wistar rats were submitted to taurocholate-induced AP and divided into three groups: Group Sham: sham-operated rats, Group Saline: AP plus saline solution, and Group PTX: AP plus PTX. Saline solution and PTX were administered 1 hour after induction of AP. At 3 hours after AP induction, peritoneal levels of tumor necrosis factor (TNF)-α, and serum levels of interleukin (IL)-6 and IL-10 levels were assayed by Enzyme-Linked Immunosorbent Assay (ELISA). Determinations of lung myeloperoxidase activity (MPO), histological analysis of lung and pancreas, and mortality study were performed. RESULTS: PTX administration 1 hour after induction of AP caused a significant decrease in peritoneal levels of TNF-α and in serum levels of IL-6 and IL-10 when compared to the saline group. There were no differences in lung MPO activity between the two groups with AP. A decrease in mortality was observed in the PTX treatment compared to the saline group. CONCLUSIONS: Administration of PTX after the onset of AP decreased the systemic levels of proinflammatory cytokines, raising the possibility that there is an early therapeutic window for PTX after the initiation of AP.